Individual differences in time-based prospective memory: the roles of working memory and time monitoring - Hemming, Wiebke; Sadus, Kathrin; Rummel, Jan (Journal of memory and language, 2025)
Time-based prospective memory (PM) refers to the ability to remember to execute an intended action at a predefined future time. Previous research suggests that both general cognitive abilities (working memory) and task specific abilities (time monitoring) underly time-based PM performance. In three studies, we investigated the relevance of specific WM processes (binding, updating) for time-based PM and unravel their interplay with task specific abilities. In Experiment 1 (N = 147), we manipulated working-memory load, and found a greater influence of time monitoring on PM performance with increasing load. In Experiment 2 (N = 132), we found, in addition to time monitoring, specifically WM updating abilities to be associated with PM performance. In Experiment 3 (N = 148), we found PM performance to suffer when updating demands were increased but the effect vanished after controlling for time monitoring. These findings emphasize the complex interplay between general cognitive ability and task specific abilities in time-based PM.
Online verfügbar: 13. November 2024
Gesehen am 14.05.2025